Paradigm shift in the area of specialised social care in Hajdú-Bihar county - Verdó, György (Acta Agraria Debreceniensis, 2012)
This paper tries to find the answer through an already working practical example how to save money on the social supporting system maintenanced by an elderly society. With the help of basic structural and organizational rearrangement, the social institutions, run by settlements and local goverments, can be helped to ran better and gain savings at the same time.